(untitled) (Shaheed Smriti Journal, 2024)
Mathematics is at the heart of business management, guiding financial decisions, strategic planning, and day-to-day operations. This study explores how businesses use mathematical concepts such as arithmetic, probability, and calculus to manage finances, optimize resources, and predict market trends. Using a qualitative document analysis approach, the research examines academic literature and industry reports to understand the role of mathematics in business success. The study analyzes financial modeling, statistical methods, and optimization techniques to highlight their impact on decision-making. Findings reveal that businesses rely on mathematics to set prices, assess risks, and forecast demand, helping them stay competitive and financially stable. Statistical tools improve efficiency, while mathematical models support marketing strategies and investment decisions. The study concludes that mastering mathematical principles enables businesses to navigate uncertainties, enhance productivity, and drive sustainable growth. By applying mathematics effectively, companies can make informed choices, streamline operations, and build a strong foundation for long-term success.